Phosphatidylinositol 3‐kinase β and β isoforms play key roles in metastasis of prostate cancer DU145 cells. Issue 11 (24th May 2018) - Zhang, Zhe; Liu, Jie; Wang, Yingying; Tan, Xiao; Zhao, Wennan; Xing, Xiaoxue; Qiu, Yuling; Wang, Ran; Jin, Meihua; Fan, Guanwei; Zhang, Ping; Zhong, Yuxu; et al.
ABSTRACT: Metastasis is the main cause of the lethality of prostate cancer. Class I phosphatidylinositol 3‐kinases (PI3Ks), which contain 4 isoforms, α, β, δ, and γ, are known to play important roles in cell growth, migration, invasion, and so on. However, the respective role of each PI3K isoform in cancer cell migration and invasion remains unknown. In a study that aimed to elucidate the respective role of the 4 PI3K isoforms, we investigated the change in migratory and invasive ability of DU145 cells after treatment with each PI3K isoform‐specific inhibitor. Both migration and invasion of DU145 cells were potently blocked by each of the PI3Kβ inhibitors (GSK2636771 and TGX221) and PI3Kδ inhibitors (CAL101 and IC87114) while not obviously affected by PI3Kα inhibitor BYL719 or PI3Kγ inhibitor AS252424. Furthermore, knocking down PI3Kβ or PI3Kδ isoform led to a significant decrease in migration of DU145. The results suggest that PI3Kβ and PI3Kδ play key roles in prostate cancer cell migration, while PI3Kα and PI3Kγ might be redundant. Oral administration of GSK2636771 (100 mg/kg) and CAL101 (30 mg/kg) inhibited tumor growth in bone, an experimental model by intratibia injection of DU145 cells, with improved bone structure and bone mineral density analyzed by micro‐computed tomography. Tissue staining indicated reduction of metastatic DU145 cells and osteoclasts in the bones of GSK2636771‐ and CAL101‐treated mice compared to the untreated group. In summary, our results indicated the distinct roles of 4 PI3K isoforms in the migration of prostate cancer DU145 cells, and they demonstrated the in vitro and in vivo antimetastatic effect of PI3K‐isoform specific inhibitors, most of which are in clinical trials.—Zhang, Z., Liu, J., Wang, Y., Tan, X., Zhao, W., Xing, X., Qiu, Y., Wang, R., Jin, M., Fan, G., Zhang, P., Zhong, Y., Kong, D. Phosphatidylinositol 3‐kinase β and δ isoforms play key roles in metastasis of prostate cancer DU145 cells. FASEB J . 32, 5967–5975 (2018). www.fasebj.org